The gender dimension of the transport workforce - Wei-Shiuen Ng; Ashley Acker (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
Women remain underrepresented in most transport-related industries, with only 17% female employees on average across a sample of 46 countries. Both attracting and retaining them remains a challenge for governments and the private sector. This study provides an in-depth analysis of the correlation between female participation in the transport workforce and variables such as GDP per capita, education and labour laws. It also provides recommendations on how to develop policies and measures that will enable gender equality in the transport workforce.
Keywords: 330; Verkehrsberufe; Weibliche Arbeitskräfte; Gleichstellungspolitik